2011
DOI: 10.4028/www.scientific.net/msf.704-705.563
|View full text |Cite
|
Sign up to set email alerts
|

Solidification and Boride Characteristics of Boron-Containing Austenitic Stainless Steel

Abstract: Differential scanning calorimetry was used to study melt and solidification and microstructure of austenitic stainless steels containing boron. The liquidus and solidus temperatures decreased because of the boron content, and boron inhibited the formation of δ-Fe. A large content of eutectic boride structure was detected when the boron content was higher. The boride was M2B, and the crystal structure was orthorhombic. The crystal structure and elemental composition of M2B were investigated in detail by SEM-EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although 1D boron substructures are arranged in 12 topological types (Tables , S3, Figures , and ), simple chains of the 2C1 topology are realized in 80% cases. In Me 5 B 6 (Me = Nb, Ta) and Cr 2 Ni 3 B 6 , two most frequent 1D motifs, 2C1 and 2,3C1, exist together, and in ErMoB 3 , the 2C1 chains coexist with the 2D hcb layers. Advantages of the topological classification are clearly seen on the example of a rare 2,3 4 C3 topology, which occur only in two borides of different structure types: U 5 Mo 10 B 24 and CeMo 2 B 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Although 1D boron substructures are arranged in 12 topological types (Tables , S3, Figures , and ), simple chains of the 2C1 topology are realized in 80% cases. In Me 5 B 6 (Me = Nb, Ta) and Cr 2 Ni 3 B 6 , two most frequent 1D motifs, 2C1 and 2,3C1, exist together, and in ErMoB 3 , the 2C1 chains coexist with the 2D hcb layers. Advantages of the topological classification are clearly seen on the example of a rare 2,3 4 C3 topology, which occur only in two borides of different structure types: U 5 Mo 10 B 24 and CeMo 2 B 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Fractography of the test specimens confirmed a dimple rupture typical for austenitic steels. It has been reported that the size and depth of dimples are closely connected with tensile toughness [27,28]. As the grain size increases, the size and the depth of dimples increase as well.…”
Section: Grain Size Effectmentioning
confidence: 96%
“…Depending on the alloying concept of austenitic stainless steel, the critical boron content is around 1 wt. %B [27]. Nonetheless, differential scanning calorimetry (DSC) was conducted to get a closer look at liquid-solid phase transformation during solidification.…”
Section: Delta Ferrite and Sigma Phase Embrittlementmentioning
confidence: 99%